Miracle Healing On Sabbath: An Exegesis Of Mark 3:1-6 - Pandeirot, Brian (Jurnal Koinonia: Fakultas Filsafat Universitas Advent Indonesia, 2025)
The Sabbath, a cornerstone of biblical theology, embodies God’s creation, sanctification, and covenant with humanity. Over time, its observance became heavily burdened with legalistic stipulations, especially during the intertestamental period. These additions distorted its purpose, culminating in tensions between Jesus and Jewish leaders, particularly the Pharisees. Mark 3:1–6 portrays a critical confrontation where Jesus heals a man with a withered hand on the Sabbath, challenging rigid interpretations while emphasizing the day’s restorative essence. Scholarly discourse reflects diverse views on this episode. Some propose that Jesus redefined the Sabbath by prioritizing humanitarian acts, while others interpret it as a confrontation against Pharisaic legalism. Prior studies lack an in-depth exploration of Mark 3:1–6 within its historical and grammatical context. This study bridges these gaps by examining Mark 3:1–6 through a historical-grammatical lens, exploring its theological implications. It hypothesizes that Jesus’ Sabbath healing reaffirms the day’s divine intent as one of restoration and salvation, countering the prevailing legalism and redefining its role in the covenantal relationship.